Quantitative Structure-Property Relationship of the Rare-Earth Elements-Dibutyl Dithiophosphate Derivative Complexes Using Principal Component Analysis - Nurdeni; Saputra, Heru Agung; Atje Setiawan Abdullah; Budi Nurani Ruchjana; Husein Hernandi Bahti; Hedi (Fine Chemical Engineering, 2024)
The separation of rare-earth elements (REEs) has increasingly developed, especially using a complexing ligand of dibutyl dithiophosphate (DBDTP) that has numerous advantages as an extractant in the extraction process. Through technology development, this separation utilizes computational chemistry design to scheme the DBDTP ligand and its derivatives. One of the computational chemistry applications is a quantitative structure-property relationship (QSPR), which is useful for designing ligand derivatives by calculating molecular descriptors and connecting molecular structure with its physicochemical properties. In the present study, we aimed to get a dominant factor affecting complex stability formed from the REEs with DBDTP ligands and the REEs with DBDTP derivative ligands using principal component analysis for the QSPR study. The analysis results demonstrated that the stability of gadolinium, terbium, and dysprosium complex compounds was influenced by seven, seven, and six factors with a total variance of 93.93, 93.17, and 91.63%, respectively.